A educação e a sociedade atual frente às novas tecnologias - Weiler, Lara (Linguagens & Cidadania, 2017)
This paper is about children’s education face new technologies. In the beginning of historic times the education and formation of children suffered changes that day by day facilitate more its cognitive development and learning in school context. The children get involved then their wishes of learning and going to school have increased. Currently, it has been discussed and invested in new technologies to education, mainly to children of elementary education that since early have contact with computerization and new technologies. The use of new technologies made possible the change of information trough participation in discussion, lists of e-mail or chats that allow to talk by computer. We can observe development of programs in away education, on- line, through computers occur communication between teacher and student the class not presence form students each time more. The facilities of access webs and advances in telecommunication change the concepts of presence and distance in education developing reasoning, creativity, intelligence and motor coordination. Learning is reorganize the structures of knowledge interacting thought styles, knowing and the know to made that occur trough dialogue process among people. Therefore, the internet has big qualities and varieties but many times occur lack of structure, orientation and instruction to its users. The use of internet in education and its development facilitated interaction of teacher, computer and student being possible to verify and organize better this system clarifying doubts and direction the student to think and learn to learn.